2019
DOI: 10.1177/1059840518824395
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and Victimization and Youth Suicide Risk: The Buffering Effects of School Connectedness

Abstract: Bullying has been linked to adolescent suicidal behavior. With dramatic increases in social media use among youth, understanding the influence of cyberbullying on adolescent suicidal behavior has become central to prevention efforts. This study examined the potential protective role of school connectedness in the relationship between cyberbullying and suicide risk behavior. Data were from 93 adolescents participating in a longitudinal study of an intervention to prevent health-risk behavior including suicidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 15 publications
5
57
0
2
Order By: Relevance
“…Numerous studies have been conducted to investigate the consequence of cyberbullying, including problems of mental and physical health [3,4,6,15,47]. Nonetheless, the potential mechanisms underlying cyber victimization and psychological and physical symptoms remain unclear, and only little research has explored this specific topic [13,21,22]. The present study is the first to show that internet addiction mediates the relationship between cyber victimization and physical and mental health, and that physical exercise plays a moderating role on the above mediation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Numerous studies have been conducted to investigate the consequence of cyberbullying, including problems of mental and physical health [3,4,6,15,47]. Nonetheless, the potential mechanisms underlying cyber victimization and psychological and physical symptoms remain unclear, and only little research has explored this specific topic [13,21,22]. The present study is the first to show that internet addiction mediates the relationship between cyber victimization and physical and mental health, and that physical exercise plays a moderating role on the above mediation.…”
Section: Discussionmentioning
confidence: 61%
“…Family dinners were proposed to moderate the relationship between cyber victimization and mental health problems [13]. In addition, connectedness between students and school was identified to function as a moderator by alleviating the association between cyber victimization and suicide [22]. This study hypothesized that victims may search for other means, such as a virtual reality to cope with the pressures of being bullied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wyman et al (2010) found that improving students' school engagement can effectively and significantly reduce their suicide-risk level. Considerable evidence has confirmed that school engagement is an important protective factor against NSSI (Chapman et al, 2011;Kim et al, 2019). Chapman et al (2011) found that emotional school engagement was associated with lower injurious behavior, including NSSI behavior in adolescents.…”
Section: School Engagement As a Potential Mediatormentioning
confidence: 99%
“…Chapman et al (2011) found that emotional school engagement was associated with lower injurious behavior, including NSSI behavior in adolescents. Moreover, Kim et al (2019) reported that emotional school engagement could buffer the negative impact of cybervictimization on adolescent NSSI and suicidal behaviors. Based on the literature reviewed above, school engagement may be a crucial mediator in the underlying mechanism that how cyberbullying victimization brings a bear to adolescent NSSI, so we propose the following:…”
Section: School Engagement As a Potential Mediatormentioning
confidence: 99%
“…Nonetheless, the potential mechanisms underlying cyber victimization and psychological and physical symptoms remain unclear, and only little research has explored this specific topic [13,21,22]. The present study is the first to show that internet addiction mediates the relationship between cyber victimization and physical and mental health, and that physical exercise plays a moderating role on the above mediation.…”
Section: Discussionmentioning
confidence: 54%